Comparative endocrinology vol, 1 - Euler , U.S. Von; Heller , H.; Hormones , Glandular (London Academic, 1963)
Comparative Endocrinology: A Treatise in Two Volumes, Volume I: Glandular Hormones focuses on animal morphology, physiology, and chemistry and systematic and comprehensive account of endocrine principles from the comparative consideration. The selection first offers information on hypothalamic control of anterior pituitary and neurohypophyseal hormones. Discussions focus on adrenocorticotropin, thyrotropin, gonadotropins, physiological significance of the neurohypophyseal hormones in mammals, and physiological significance of the neurohypophyseal hormones in nonmammalian vertebrates. The text then takes a look at pituitary hormones affecting chromatophores and female gonadal hormones. The publication examines male gonadal hormones and adrenocortical hormones. Topics include action of testicular estrogen and ovarian testosterone, source of sex hormones in the male, factors regulating testicular functions, biochemistry of androgens, and functions of the adrenocortical hormones. The book then tackles chromaffin cell hormones, thyroid hormones, and parathyroid glands. The selection is a dependable source of data for readers interested in glandular hormones.
Keywords: Biology